GAS CHROMATOGRAPHY-MASS SPECTROMETRY ANALYSIS OF THE HEXANE FRACTION OF THE AERIAL PARTS OF LIMONIUM OTOLEPIS (Scientific journal of the Fergana State University, 2025)
This article presents the results of the gas chromatography-mass spectrometry analysis of the hexane fraction of the aerial parts of the halophytic plant Limonium otolepis, which is distributed in the desert areas of the Fergana Valley region. According to the results, a total of 74 compounds were identified in the hexane fraction. Among them, 9 compounds were found to make up 92.51% of the total fraction. The highest amounts were recorded for Carbonic acid eicosyl vinyl ester, n-Pentacosane, n-Docosane, n-Nonadecane, and n-Heneicosane, with respective concentrations of 43.923%, 25.151%, 12.34%, 4.94%, and 3.456%.